Path Analysis on the Psychosocial Impact of Obesity or Overweight in Adolescents in Surakarta, Central Java - Yayang Kharistik A; Yulia Lanti Retno Dewi; C.S.P. Wekadigunawan (Masters Program in Public Health, 2018)
Background: Worldwide obesity shares 33 percent of adolescents body mass index. The prevalence of obesity has increased threefold since 1980. In Indonesia there are 10.8 percent of children aged 13-15 years who are obese. Obesity and overweight can cause various chronic diseases. Another important impact is psychosocial. Correct intervention and early prevention can reduce the psychosocial impact. This study aimed to determine the psychosocial impact of obesity or overweight on adolescents. Subjects and method: This was an analytic observational study with cross-sectional design. The study was conducted at 6 junior high schools in Banjarsari and Jebres, Surakarta, Central Java, from October to November, 2017. A total sample of 160 junior high school students were selected for this study by purposive sampling. The dependent variables were depression, self-assessment, body image, eating disorder, and quality of life. The independent variables were obesity or overweight. Body mass index (BMI) was measured by body weight scale and microtoise. Data of other study variables were collected by questionnaire. The data were analyzed by path analysis.Results: Obesity or overweight was directly associated with depression (b= 1.04; 95% CI= 0.32 to 1.77; p= 0.005) and bad body image (b= -2.35; 95% CI= -3.20 to 1.49; p< 0.001). Depression was directly associated with eating disorder (b= 0.55; CI 95%= -0.87 to 1.18; p=0.091) and poorer quality of life (b= -0.64; 95% CI= -1.34 to 0.69; p= 0.077). Good body image was directly asssociated with positive self-assessment (b= 2.71; 95% CI= 1.89 to 3.52; p<0.001).Conclusion: Obesity or overweight in adolescents is directly asssociated with depression and bad body image. Obesity or overweight is indirectly associated with negative self-assessment, eating disorder, and poorer quality of life.Keyword: overweight, obesity, psychosocial, path analysisCorrespondence: Yayang Kharistik Almasith. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: ycharistik@yahoo.com. Mobile: +6281229474445Journal of Epidemiology and Public Health (2018), 3(2): 105-117https://doi.org/10.26911/jepublichealth.2018.03.02.01